SF‐6Dv2 preference value set for health utility in food allergy. Issue 1 (6th July 2020) - Dufresne, Élise; Poder, Thomas G.; Samaan, Kathryn; Lacombe‐Barrios, Jonathan; Paradis, Louis; Des Roches, Anne; Bégin, Philippe
Abstract: Background: The lack of a value set allowing the calculation of QALY is an important limitation when establishing the value of emerging therapies to treat food allergy. The aim of this study was to develop a Short‐Form Six‐Dimension version 2 (SF‐6Dv2) preference value set for the calculation of health utility from the Canadian food‐allergic population. Methods: Two hundred ninety‐five parents of patients aged 0‐17 years old and 154 patients aged 12 years old and above with food allergy were recruited in clinic and online. Participants were asked to complete a self‐administered online questionnaire including generic health‐related quality of life questionnaires. Various health states described by the SF‐6Dv2 were valued with time‐trade‐off and discrete choice experiments. Data from elicitation techniques were combined using the hybrid regression model. Results: A total of 241 parents and 125 patients performed 3904 time‐trade‐off and 5112 discrete choice experiments. Utility decrements were estimated for each level of each SF‐6Dv2 dimension. Utility values calculated based on the validated preference set were in average 0.15 lower (95%CI: 0.12‐0.18) and were poorly correlated ( R 2  = 0.46) with those derived from the EQ‐5D‐5L generic questionnaire in the same cohort. Conclusion: A representative preference value set for patients with food allergy was determined using the SF‐6Dv2 generic questionnaire. This adapted preference set will contribute to improve the validity of future utility estimates in this population for the appraisal of upcoming potentially impactful but sometimes costly therapies. Abstract : There is currently no validated instrument to calculate health utility in food allergy, which is a barrier to the conduct of cost‐effectiveness analyses. Using time trade‐off and discrete choice experiment approaches, options of the SF‐6Dv2 generic health‐related quality of life questionnaire were directly valued in the Canadian food allergic population. The resulting algorithm based on the health preferences of food allergic patients and parents can now be used to convert SF‐6Dv2 answers to health utility values in this population. Abbreviation: SF‐6Dv2, Short form‐six dimensions version 2.